Enhancing Health Literacy and Self-Care Abilities among Individuals with Chronic Diseases - Kadar, Kusrini (Faculty of Nursing, Universitas Hasanuddin, 2024)
Health literacy is an essential element in the effective management of chronic diseases. It provides a foundation for individuals to understand, evaluate, and utilize health information, thus enabling them to make well-informed decisions regarding their care. For individuals living with chronic conditions such as diabetes, heart disease, and hypertension, health literacy is not just about understanding their health needs; it is about empowering them to manage their conditions effectively, make informed healthcare decisions, and maintain a higher quality of life. This writing explores the multidimensional relationship between health literacy and self-care abilities among people with chronic diseases, examining the factors affecting health literacy, its impact on self-care, strategies for improvement, and the pivotal role of health professionals in this context.